VD_FINDINFO Faillite / 2017 / 20 vom 13. Juli 2017 - VD Tribunal cantonal (2017)
OUVERTURE DE LA FAILLITE, INSOLVABILITÉ, SUSPENSION DE LA PROCÉDURE | 174 al. 2 LP, 174 LP, 126 al. 1 CPC (CH), 126 CPC (CH)